Kwatha Kalpana: It’s Versatility with Probable Advancement - Meena, Dr. Vandana (Asian Journal of Pharmaceutics (AJP), 2018)
Gigantic mushroomic bloom of Ayurvedic pharmaceutical industries has raised a big question mark on standardization parameters at each stage of manufacturing process. Kwatha Kalpana being the most considerable and extensively used dosage form in Ayurvedic pharmaceutics has some disadvantages in certifying the quality control of the herbal ingredients, time duration, and inconvenience required in preparation, transportation, and storage. This hindrance diminishes compliance and may hamper with the management of processing of drugs. Various pharmaceutical factors are needed to be monitored such as vessel’s dimension, temperature, proportion of water, particle size of crude drug, duration, and quantum of heat. Due to globalization, development in its different dosage form is needed without compromising the therapeutic efficacy. The dosage form is being modified and improved from decoction (liquid) to kashaya powder, rasakriya, ghana, tablets, capsules, syrup, and Pravahi kwatha. This conversion has many advantages over kwatha preparation, i.e., acceptability and prolong shelf life. Hence, the present paper discusses necessitate and proper advancement for pharmaceutical standardization of kwatha to optimize the regulating factors to maintain uniformity in pharmaceutical industries for universal acceptance.